ANALISIS BENTUK FUNGSI DAN MAKNA SIMBOL MOTIF PADA SARUNG ADAT ENDE LIO DENGAN KAJIAN SEMIOTIKA - Jima, Helena; Djuli, Labu; Makan Malay, Narantoputrayadi (Jurnal Lazuardi, 2025)
This study aims to identify and describe the meanings and symbolic motifs of the Ende Lio traditional sarong. The focus of this research is on the form, function, and symbolic meaning of the motifs found in these traditional sarongs. The study applies semiotic theory, which explains the process of examining and analyzing signs and cultural symbols.A qualitative method was employed, as the research object was studied in its natural cultural context. The analysis reveals that the symbols found in Sarung Kelimara, Sarung Jara Elo, Sarung Redu Siku Mbira, and Sarung Pundi each possess distinct forms, functions, and meanings. However, they all share aesthetic values that reflect the unique cultural identity of Ende Lio.This research is expected to serve as a reference for future studies in linguistics and cultural semiotics, as well as contribute to the preservation of Ende Lio’s local culture.